2021
DOI: 10.3389/fncir.2021.643360
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis for Theta Rhythm Frequency Control in CA1 Microcircuits

Abstract: Computational models of neural circuits with varying levels of biophysical detail have been generated in pursuit of an underlying mechanism explaining the ubiquitous hippocampal theta rhythm. However, within the theta rhythm are at least two types with distinct frequencies associated with different behavioral states, an aspect that must be considered in pursuit of these mechanistic explanations. Here, using our previously developed excitatory-inhibitory network models that generate theta rhythms, we investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…However the mechanisms were separate in that the coupling to produce coherent theta did not itself also generate gamma and thus somewhat different to the current model. Of course we do not mean to suggest that slow oscillations themselves cannot be generated by different means (for example [ 14 , 36 , 92 94 ]) or that PAC cannot be generated by different means. Indeed a recent model demonstrates PAC emergence in a completely different way using a spatial dimension [ 95 ].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However the mechanisms were separate in that the coupling to produce coherent theta did not itself also generate gamma and thus somewhat different to the current model. Of course we do not mean to suggest that slow oscillations themselves cannot be generated by different means (for example [ 14 , 36 , 92 94 ]) or that PAC cannot be generated by different means. Indeed a recent model demonstrates PAC emergence in a completely different way using a spatial dimension [ 95 ].…”
Section: Discussionmentioning
confidence: 94%
“…Hippocampal theta is often found around 8 Hz in-vivo but there are also known to be at least two types of in-vivo hippocampal theta, low (3-7 Hz) and high (7-12 Hz) [ 14 ]. Social stimuli elicit high theta, and fearful stimuli elicit low theta [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We built upon earlier modeling studies that brought together minimal ( Ferguson et al, 2017 ) and detailed ( Bezaire et al, 2016b ) CA1 microcircuit models with defined inhibitory cell types that produce theta rhythms and showed that large enough PYR cell networks could initiate theta rhythms with inhibitory cell populations ‘regularizing’ the rhythm. We termed this an ‘inhibition-based tuning’ mechanism ( Chatzikalymniou et al, 2021 ; Skinner et al, 2021 ). The theta rhythm generation is initiated by the PYR cell population which also sets the theta frequency, but the termination of the theta bursts is an inhibition-mediated mechanism which contributes to the robustness and stability of the rhythm.…”
Section: Discussionmentioning
confidence: 99%